Teaching Across Disciplines: Challenges and Strategies of Multi-Subject Teachers in Elementary Education - Nirwati Nirwati; Sella Nofriska Sudrimo; Lestari Handayanti (MISOOL: Jurnal Pendidikan Dasar, 2025)
This study aims to examine in depth the challenges and strategies employed by multi-subject teachers in carrying out the teaching and learning process at SD Nurul Sakinah Azzahrah, Sorong City. The emergence of multi-subject teachers is a consequence of the limited number of educators, requiring one teacher to handle several subjects beyond their area of expertise. This research applied a descriptive qualitative method, with data collected through in-depth interviews, classroom observations, and documentation review. The findings reveal that teachers face several major challenges, including limited time for lesson preparation, varying levels of subject mastery, and a lack of learning media and facilities. Nevertheless, teachers demonstrate adaptability by employing strategies such as utilizing simple technology, creating context-based learning materials from the local environment, and adjusting instructional approaches to students’ characteristics. Support from school leadership and collaboration among teachers also enhance the effectiveness of learning. The study concludes that creativity, professional reflection, and strong commitment are key factors in ensuring the success of multi-subject teachers in maintaining learning quality in elementary schools with limited resources.